Measured and Predicted Basal Metabolic Rate in Inflammatory Bowel Disease Patients. (29th May 2020) - Anjos, Luiz Dos; Campos, Tatiana; Dantas, Juliana; Fernandes, Fernanda; Wahrlich, Vivian
Abstract: Objectives: To measure basal metabolic rate (BMR) and to compare the values with estimated BMR from international and local predictive equations in inflammatory bowel disease (IBD) patients. Methods: A total of 72 (38 women) subjects with Chron's disease ( n  = 45, 19 women) and ulcerative colitis ( n  = 27, 19 women) from an outpatient care unit in Rio de Janeiro, Brazil, agreed to participate in the study. Anthropometric measures were obtained using standard procedures. Percent body fat (PBF) was assessed by DXA. BMR was measured (BMRm ) by indirect calorimetry (Vmax Encore 29) under standardized conditions and compared with BMR estimated by internationally-recommended (Schofield, 1985) and locally-developed (Anjos et al., 2014) predictive equations. Bias was calculated as estimated - measured BMR. Results: The mean ± SD (range) age was 38.0 ± 11.3 (20.1 – 58.3) years with a mean BMI of 24.7 ± 4.5 (16.1 – 39.1) kg.m −2 and PBF of 32.2 ± 9.1 (9.7 – 53.4). BMRm was significantly lower in women (1169.3 ± 205.0) than men (1439.0 ± 197.5) kcal.day −1 . The Schofield's equations significantly overestimated BMR for both women (bias of 204.0 ± 148.3 kcal.day −1 or 17.4%) and men (306.7 ± 171.0 kcal.day −1 or 21.3%). The locally-developed equation yielded nonsignificant estimates for both women (−5.8 ± 143.7 kcal.day −1 or −0.5%) and men (−19.9 ± 165.5 kcal.day −1 or −1.4%). Conclusions: The findings of the present study indicate that internationally-recommended BMR predictive equations are not accurate to estimate BMR in IBD patients in a tropical setting. As observed in samples of healthy adults from the same city, the locally-developed BMR equations yield unbiased and accurate estimates for IBD patients. Funding Sources: CNPq (310, 461/2016–20) and FAPERJ (E-26/202.514/2018; E-26/203.068/2018; E-26/203.068/2017; E-26/202.520/2016; E-26/210.747/2016).